Genetic Variability, Heritability and Genetic Advance Estimates in Sunflower (Helianthus annus L.) Genotypes at Holetta and Adadi, Ethiopia - Abu, Mohammed (International Journal For Research In Agricultural And Food Science, 2020)
The present study was conducted with twenty five sunflower genotypes including one check at two locations, Holetta and Adadi to study genetic variability, heritability and genetic advance for seed yield and yield related components. The experiment was conducted using 5x5 simple lattice design across two locations during 2017/18 main cropping season. Data were recorded for fifteen quantitative traits and subjected to statistical analysis using a combination of statistical software by following different biometricians. The pooled analysis of varience revealed that significant differences (P<0.05) for all traits except for petiole length, stem diameter and ray floret number. High phenotypic coefficients of variation were observed for oil yield and seed yield per hectare. Medium genotypic coefficients of variation were recorded for oil yield and number of seed per plant whereas, Low genotypic coefficients of variation were observed for the remaining traits. Heritability in broad sense ranged from low for seed yield per plant to high for oil content. High heritability along with high genetic advance was observed for number of seed per plant.